The aesthetic phenomenon as communication: Construction of meaning and reality in cinematographic art - Pita Dueñas, César (2022)
Art is an aesthetic and communicative phenomenon. Under this premise, the purpose of this paper is to link both dimensions and understand how reality is constructed from cinematographic point of view. We start from Palazon’s approaches to aesthetic studies and relate them to the construction of sense and generation of reality from artistic perspective, based on authors such as Heidegger, Sánchez Vásquez and Plazaola. This allows us to get closer to André Bazin’s strictly cinematographic ideas. As a construction of recognizable reality, representation in cinema is more verisimilar due to a mediation process that results from communicative act.